Design thinking for tech : solving problems and realizing value in 24 hours - Anderson, George W. (Software architect) (Rough cuts (Pearson), 2022)
In just 24 lessons of one hour or less, Design Thinking for Tech helps you inject techniques and exercises into your projects using the same systematic and creative process that designers have used for years. Anderson walks you through a simple four-phase Design Thinking model, showing how to loop back, keep learning, and continuously refine your work. Youll start by understanding the essential what, how, when, why, and who of Design Thinking. Next, youll use core Design Thinking techniques to understand the big picture, focus on your most critical problems, think more creatively about them, take the "next best steps" toward problem resolution and value creation, and along the way rapidly iterate for progress. Every lesson builds on what youve already learned, with exercises crafted to deliver directly relevant experience. Regardless of your role in the world of technology, youll learn how to supercharge success for any tech-related project, business initiative, or digital transformation.